The nitrogen isotope effect of benthic remineralization-nitrification-denitrification coupling in an estuarine environment - M. Alkhatib; M. F. Lehmann; P. A. del Giorgio (Biogeosciences, 2012)
The nitrogen (N) stable isotopic composition of pore water nitrate and total dissolved N (TDN) was measured in sediments of the St. Lawrence Estuary and the Gulf of St. Lawrence. The study area is characterized by gradients in organic matter reactivity, bottom water oxygen concentrations, as well as benthic respiration rates. N isotope effects on the water column associated with the benthic exchange of nitrate (εapp) and TDN (εsed) during benthic nitrification-denitrification coupling were investigated. The sediments were a major sink for nitrate and a source of reduced dissolved N (RDN = DON + NH4+). We observed that both the pore water nitrate and RDN pools were enriched in 15N relative to the water column, with increasing δ15N downcore in the sediments. As in other marine environments, the biological nitrate isotope fractionation of net fixed N loss was barely expressed at the scale of sediment-water exchange, with ϵapp values <3‰. The strongest under-expression (i.e. lowest εapp) of the biological N isotope fractionation was observed at the most oxygenated sites with the least reactive organic matter, indicating that, through their control on the depth of the denitrification zone, bottom water oxygen concentrations and the organic matter reactivity can modulate εapp. For the first time, actual measurements of δ15N of pore water RDN were included in the calculations of εsed. We argue that large fractions of the sea-floor-derived DON are reactive and, hence, involved in the development of the δ15N of dissolved inorganic N (DIN) in the water column. In the St. Lawrence sediments, the combined benthic N transformations yield a flux of 15N-enriched RDN that can significantly elevate εsed above εapp. Calculated εsed values were within the range of 4.6 ± 2‰ and were related to organic matter reactivity and oxygen penetration depth in the sediments. ϵsed reflects the δ15N of the N2 lost from marine sediments and thus best describes the isotopic impact of fixed N loss from sediments on the oceanic fixed N pool. Our mean value for εsed is larger than assumed by earlier work, questioning current ideas with regards to the state of balance of the modern N budget.